EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA PENINGKATAN KETERAMPILAN HIGHER ORDER THINKING SKILLS (HOTS) SD NEGERI 173531 MEAT - Simbolon, Novi Tari; Simamora, Indah; Br Sinuraya , Fitri Rohayati (Jurnal Ilmiah Aquinas, 2025)
The purpose of this study was to determine whether the problem-based learning paradigm is useful in improving high-level thinking skills or high-level thinking skills of students of SD Negeri 173531 MEAT Mathematics in the 2024-2025 academic year. This study uses a quasi-experiment as its research methodology. The population of the study was all students of SD Negeri 173531 MEAT Mathematics in the 2024-2025 academic year. The data collection method used a control class and an experimental class. The data collection method in this study used a pretest and posttest. The data analysis method used was the t-test (Independent sample T-Test). In addition, to determine the increase, an n-gain test was carried out. The research findings show that (1) the Problem-Based Learning Model is useful for improving high-level thinking skills (HOTS) or high-level thinking; (2) indicators of knowledge transfer, critical thinking, and problem solving are in the high, medium, and medium categories, respectively